2017
DOI: 10.1111/gcbb.12454
|View full text |Cite
|
Sign up to set email alerts
|

Net ecosystem fluxes and composition of biogenic volatile organic compounds over a maize field–interaction of meteorology and phenological stages

Abstract: Bioenergy crop production is rapidly expanding in Europe, and the potential emissions of biogenic volatile organic compounds (BVOCs) might change the chemical composition of the atmosphere, influencing in turn air quality and regional climate. The environmental impacts of bioenergy crops on air chemistry are difficult to assess due to a lack of accurate field observations. Therefore, we studied BVOC fluxes from a bioenergy maize field in North-Eastern Germany throughout the entire reproductive growth stage of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 83 publications
(153 reference statements)
0
17
1
Order By: Relevance
“…for Miscanthus spp, for grassland, for maize and for maize, respectively. Also, while methanol exchange rates reported in this study were more than 6-fold more substantial than in the maize study of Wiß et al (2017), acetone and acetaldehyde exchange rates were 5 to 10-fold less important.…”
Section: Comparison Of Ovoc Exchange Rates With Other Herbaceous Cropscontrasting
confidence: 74%
See 2 more Smart Citations
“…for Miscanthus spp, for grassland, for maize and for maize, respectively. Also, while methanol exchange rates reported in this study were more than 6-fold more substantial than in the maize study of Wiß et al (2017), acetone and acetaldehyde exchange rates were 5 to 10-fold less important.…”
Section: Comparison Of Ovoc Exchange Rates With Other Herbaceous Cropscontrasting
confidence: 74%
“…It is well known that OVOC exchanges are bi-directional (Jardine et al, 2011(Jardine et al, , 2008Kesselmeier et al, 1998;Niinemets et al, 2014;Wohlfahrt et al, 2015), and that cold and wet conditions favour uptake, whereas warm and dry conditions rather favour emission. Several studies have reported methanol (Laffineur et al, 2012;Wiß et al, 2017;Wohlfahrt et al, 2015), acetaldehyde (Jardine et al, 2008) or acetic acid uptake (Jardine et al, 2011) under wet and/or cold conditions, including at the LTO site (Bachy et al, 2016). In particular, bi-directional methanol exchanges were measured for bare soil at the LTO site, and analyses indicated that Fig.…”
Section: Ovoc Uptake Under Cold Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wiß et al, 2017), not only in deciduous plant species but also in evergreens, which 5 retain their foliage for several years. In evergreens, the development of new buds and foliage occurring in spring is characterized by conspicuously high emissions of monoterpenes, methanol and some other VOCs (Aalto et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different types of plants (mainly Cannabis sativa and Cannabis indica) at different growing stages and conditions (soil type, light, fertilization, watering, ventilation, size of pots, concentration of CO 2 in grow rooms, relative humidity, temperature, etc.) may release BVOCs in various ratios (Niinemets, Loreto, and Reichstein 2004;Riedlmeier et al 2017;Wiß et al 2017). Knowing the ERs of BVOCs per plant, the non-BVOC concentrations in the facilities, the release of these emissions into the air, and the concentrations of NOx around the facilities can help estimate the impact of Cannabis grow facilities on air quality and develop optimal air pollution control strategies in the future.…”
Section: Resultsmentioning
confidence: 99%